Scriptural Authority in Early Judaism and Ancient Christianity (De Gruyter, 2013)
The impact of earlier works to the literature of early Judaism is an intensively researched topic in contemporary scholarship. This volume is based on an international conference held at the Sapientia College of Theology in Budapest, May 18-21, 2010. The contributors explore scriptural authority in early Jewish literature and the writings of nascent Christianity. They study the impact of earlier literature in the formulation of theological concepts and books of the Second Temple Period
10.1515/9783110295535
Keywords: Antikes Judentum; Autorität; Bibelrezeption; Deuterocanonical literature; Deuterokanonische Literatur; Second Temple Judaism; bible reception; scriptural authority; Frühchristentum; Frühjudentum; Literatur; RELIGION / Biblical Criticism & Interpretation / Old Testament